DEMOCRATIC LIBERAL PEACE: FROM PEACE TO WAR - Afonso, Henrique Weil (Revista Ética e Filosofia Política, 2018)
Democratic Peace Theory acknowledges the spread of democratic values as a means to achieve international peace. By drawing on a comprehensive Kantian background, the theory has served as justification for the imposition of western liberal values around the globe. This article exams the theory’s basic tenets and facets in order to investigate its ideological claims. It is suggested that the spread of democratic values alone cannot be granted complete success in the task of bringing about world peace and stability. Despite its supposedly peaceful ultimate intentions, the theory may also work as a domination discourse that foments war and conflict.